Citation Classics in Urban Sociology: Mapping the Intellectual Evolution of a Research Specialty. Issue 3 (3rd July 2017) - Conte, Jill A.
Abstract: This study identifies, describes, and analyzes the most highly cited works in the urban sociology literature to investigate empirically the subfield's intellectual foundations, its future research directions, and its relationship to the broader discipline of sociology. The findings show that these landmark publications are more likely to be authored by United States based scholars, study cities in the United States, propose new concepts, and address the topic of racial inequality. They include works of classical sociology, traditional urban sociology, and new urban sociology. This study concludes that the Chicago School's legacy continues to shape contemporary urban sociology as the specialty expands in interdisciplinary directions.